Bioreactors in Hungary - Sinóros-Szabó Jr., Botond; Maniak, Stephan (Acta Agraria Debreceniensis, 2005)
The transformation and utilization of organic materials must occur with the highest degree of environmental conformity. This conformity – in accordance with the guiding principles of the European Union – will result in a new economic and systematical approach. We can establish the profitability of projects with the utilization of surplus effects which characterize multiple-product lines.